1980-1981 ネン ドライバレー チイキ チョウサ ホウコク - 中谷, 周; ナカヤ, シュウ; 鳥居, 鉄也; トリイ, テツヤ; 長, 連英; チョウ, ツラヒデ; 和田, 英太郎; ワダ, エイタロウ; 松本, 源喜; マツモト, ゲンキ; Nakaya, Shyu; Torii, Tetsuya; et al. (1982)
P(論文) 1980-1981年のドライバレー地域における地球科学的調査活動は1980年11月から1981年1月まで, ライト谷, テイラー谷を中心に行った。ライト谷のバンダ湖, ドンファン池, カノーパス湖, 上部ライト谷ラビリンス地区の4池, テイラー谷のボニー湖, ハウス湖およびこれら湖沼周辺の湖沼水, 流入水を採取するとともにバンダ湖, ボニー湖では湖底堆積物を採取した。特に, バンダ湖, ボニー湖では現地にて溶存酸素, 栄養塩類(NO_2-N, NO_3-N, NH_4-N, PO_4-P, SiO_2-Si)等を測定した。また, これらの湖沼周辺で多数の塩類堆積物, エバポライト等も採取した。バンダ湖ではオニックス川流入による水温分布変化も観測した。さらに, ロス島バード岬のペンギンルッカリー周辺の藻類等も採取した。 Five Japanese geochemists visited Scott Base and the Dry Valleys area to carry out the geophysical and geochemical research programs for a period from December 1980 to January 1981. The main research subjects in this season were; 1) geophysical study of water temperature of Lake Vanda, 2) determination of stable nitrogen isotope ratio, ^<15>N/^<14>N, of the sediments and lake waters in the Dry Valleys area and at a penguin rockery in Ross Island, 3) distribution of organic matters in the sediments and lake waters, 4) geochemical studies on the fresh and saline lakes, and distribution of evaporites in the Dry Valleys area. departmental bulletin paper